Model Tata Kelola Pemerintahan Adaptif: Pengembangan Kampung Hijau Berbasis Kebijakan Kabupaten Hijau Siak - Ferlan, Margina; Marta, Auradian; Muhammad Amin, Raja (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2025)
Green Villages are a strategic approach to promoting sustainable development, especially in tropical peat areas. This initiative is part of the Green Regency Siak policy in response to the importance of community-based environmental governance in achieving the Sustainable Development Goals (SDGs). However, in-depth studies related to the adaptive governance model in this policy are still limited, both from a theoretical and empirical perspective. This study uses a descriptive qualitative approach with case studies in several villages in Siak Regency that have implemented Green Villages. Data were collected through in-depth interviews, document studies, and participatory observations, and then analyzed thematically using the theoretical framework of adaptive governance. The results of this study found that the adaptive governance model in Siak Regency consists of four main dimensions, namely, multi-actor participation, institutional flexibility, integration of local knowledge, and response to environmental dynamics. Its implementation includes village regulations, restoration programs, and ecological fiscal incentives. This study concludes that the success of Green Villages is largely determined by local adaptive capacity and cross-sectoral support. A collaborative and social learning-based governance framework is needed in dealing with the complexity of sustainable peat ecosystem management